Understanding Kenya's Innovation System - Ogot, Madara; Muriuki, Rita; Waema, Timothy Mwololo; Omwansa, Tonny; Kably, Nathan; Reid, Benjamin (University of Nairobi and NESTA, 2020)
This report highlights the challenges and priorities of innovation policymakers in Kenya. The main findings provide an understanding and interpretation of the Kenyan science, technology and innovation system. The report is the culmination of many conversations and interviews with different innovation policymakers in the Kenyan innovation system, across several government departments. This report includes quotes from conversations that have been kept anonymous.
Keywords: Innovation; Policy; Kenya